Models and Their Limitations in the Voltammmetric Parameterization of the Six‐Electron Surface‐Confined Reduction of [PMo12O40]3− at Glassy Carbon and Boron‐Doped Diamond Electrodes. Issue 21 (13th November 2019) - Robinson, Martin; Ounnunkad, Kontad; Zhang, Jie; Gavaghan, David; Bond, Alan M.
Abstract: In acidic media, three well‐defined surface confined overall two electron transfer reactions derived from closely spaced one‐electron steps are observed in the DC and AC voltammetry of [ PMo 12 O 40 ] 3 - . In this study, parameterization of these processes by sinusoidal AC voltammetry at glassy carbon (GC) and boron doped diamond (BDD) electrodes has been undertaken in 1 M HClO4 . The experiment‐simulation comparison of even a simplified reaction scheme required estimation of 21 parameters, which is an exceptionally large number in voltammetry. The six reversible potentials were robustly recovered from data obtained at low (9.02 Hz) and higher (60.05 Hz) frequencies at both GC and BDD electrodes. Examination of the harmonic content by the Fourier transformed version of AC voltammetry enabled imperfections in the model associated with faradaic and non‐faradaic aspects of the voltammetry to be readily detected. After consideration of these imperfections, all processes were considered to be reversible within experimental uncertainty. Subtle differences in reversible potentials observed at both electrodes account for electrode dependence in shapes of the overall two electron steps. Fits of experimental data were superior using BDD at both frequencies and for the higher frequency GC case. Non‐compliance with an assumed potential independent model of the double layer capacitance was considered to be a significant contributor to discrepancies found with the GC electrode. Abstract : Quasi‐reversible versus reversible electron transfer. Parameterisation of the six‐electron reduction of surface‐confined [pMo12 O 40 ]3‐ is undertaken at GC (left) and BDD (right) electrodes. Imperfections in modelling are elucidated.